Recent Economic Developments, Prospects, and Progress in Institution Building in the West Bank and Gaza Strip - Zavadjil, Milan (International Monetary Fund, 1997)
Since the Declaration of Principles on Interim Self-Governing Arrangements between the Palestine Liberation Organization and Israel, which outlined the gradual future transfer of responsibility to the Palestinian Authority in the West Bank and Gaza Strip, the IMF has provided a wide range of technical assistance to the Palestinian Authority. This publication, by the Middle Eastern Department, reviews economic and institution building developments in the West Bank and Gaza Strip in 1996 and assesses briefly the prospects for 1997. Individual chapters describe fiscal, monetary, and external developments; trade policy; and IMF technical assistance.